In vitro shoot regeneration of Mas Cotek (Ficus deltoidea Jack) a valuable Malay medicinal plant - Abdullah Ripain, Ilfah Husna; Vikram, Paritala; Kayat, Fatimah; Susanto, Dwi; Mohammed Aurifullah (Universiti Malaysia Kelantan, 2015)
Mas Cotek (Ficus deltoidea) is one of the famous Malay medicinal plants and it is categorized as a priority herb under Entry Point Project 1 (EPP1) of National Key Economic Area (NKEA) Agriculture. Different parts of the plant had been used traditionally to treat various ailments. Due to over-exploitation, the population of many medicinal plants in the nature including Mas Cotek is decreasing day by day. This causes a big challenge to the pharmaceutical and herbal industries as they will run out of the source of plant material to support the demand from the consumers. Hence the present study aims to produce a protocol on shoot regeneration of Mas Cotek by using plant tissue culture. Mature nodes of the plant were aseptically cultured onto Murashige and Skoog (MS) media supplemented with different concentrations and combinations of plant growth regulators like 1.0-3.0 mg/l Kinetin, 1.0-3.0 mg/l BAP, 1.0-3.0 mg/l Kinetin+0.5-1.5 mg/l NAA and 1.0-3.0 mg/l BAP+0.5-1.5 mg/l NAA. 3.0 mg/l BAP was the best medium for shoot regeneration of Mas Cotek as it can produce more shoots either when used singly or in combination with NAA respectively. For the fastest shoot regeneration, MS media with 1.0 mg/l BAP + 0.5 mg/l NAA was more favourable since it can produce shoot within 4 weeks. The protocols developed under this study are highly useful for the mass clonal propagation of Mas Cotek as well as to conserve this valuable medicinal plant for future use.